Student Opinions on Task-Based Approach as Formative Evaluation versus Exam-Based Approach as Summative Evaluation in Education - Levent Uzun; Şevval Ertok (Sakarya University Journal of Education)
The present study investigated ELT students’ opinions about the convenience of exam-based or task-based approaches for their learning process, concerning three criteria that relate to the effectiveness of task-based and exam-based education: 1. the contribution to the professional and personal development of the students (whether task-based or exam-based applications develop them better); 2. the contribution to their critical and creative skills; and 3. the advantages and disadvantages of task-based and exam-based approaches. Exam-based approach as summative assessment type and task-based approach as formative assessment type were compared in terms of their advantages and disadvantages. Findings indicate that the majority of the students are not satisfied with the summative assessment system. Participants believe that the formative evaluation approach is more appropriate for them. The results propose that the conventional approach, which is based on an exam-focused system in the English Language Teaching Department, should be changed in order to enhance future English teachers’ creative skills as well as their personal and professional development as far as possible.